The Radiological Findings in an Infant Suffering from Osteopetrosis Due to a Novel Variant in the CLCN7 Gene - Davut Ünsal Çapkan; Baver Demir; Hasan Baş; Mansur Tatlı; Murat Doğan; Ekrem Ünal (The Journal of Pediatric Academy)
.